PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MTSS AL “ FURQAN - Zaki, Muhammad; Nuryadin, Rusmin; Amartana, Amartana; Marwan, Marwan; Amiruddin, Amiruddin (JGK (Jurnal Guru Kita), 2023)
The Role of the Principal in Improving the Quality of Education at Mtss Al-Furqan. Schools as an open system must be able to innovate in order to maintain their existence. The principal as a leader who holds full responsibility must be able to take steps to improve the quality of education. The purpose of this study is to describe the role of the principal of MTsN 9 Kuta Blang: (1) the role of the principal as an educator in improving the quality of education, (2) the role of the principal as an administrator in improving the quality of education, (3) the role of the principal as a manager in improving the quality of education, (4) the role of the principal as a supervisor in improving the quality of education. The method used in this research activity is a qualitative approach with a type of literature study research. The results obtained from research activities are the role of the principal which needs to be further developed in order to achieve the expected quality of education at MTSs Al-Furqan. So it is necessary to develop the role of the principal as an educator, administrator, leader, and regulator. The conclusions obtained from this research activity prove that the role of the Principal in Improving the Quality of Education at MTSs Al-Furqan, that is, even though the role of the school principal is good, it still needs to be improved based on the role that exists in the research objectives.
Keywords: Principal; Quality of Education